Economic Diplomacy Strategy in Increasing Globally Competitive National Food to Realize a Golden Indonesia 2045 - Mulya, Hikmatul Fajri; Lukman Yudho Prakoso; Suwito, Suwito (CV. AFDIFAL MAJU BERKAH, 2024)
Economic diplomacy strategies are very important in establishing cooperation aimed at improving national economic development. Currently, food has become a commodity that is needed by every country to meet its country's needs. This can be maximized by Indonesia to compete globally to improve the quality of national food where Indonesia is a country that has abundant natural resources. The existence of global national food competitiveness helps economic growth so that it can improve people's welfare and make Indonesia golden in 2045. This research uses Economic Diplomacy Theory according to Kishan S. Rana (2007) divides the typology of economic diplomacy into four types, namely traditional, niche-focused, evolving, and innovative. The research aims to explain Indonesia's economic diplomacy strategy in increasing national food that is globally competitive to realize golden Indonesia 2045. The research uses a literature study method that involves analysis of relevant written sources. The results achieved show that economic diplomacy strategies are very important in improving national food that is globally competitive with careful and intelligent government policies in facing challenges and preparation in improving the quality of national food.